Analysis Of The Competitiveness Of Robusta Coffee Is Reviewed From The Perspective Of International Trade Law - Perdana, Andre Pebrian; Ratna, Ratna Fitriyani; Maulana, Maulana Yusuf; Meta, Meta Aryani (Jurnal Hukum Malahayati, 2024)
In global trade, robusta coffee plays a central role as an important commodity in the economies of major producing countries. This article explores the analysis of the competitiveness of robusta coffee from the perspective of international trade law, exploring the factors that influence its position and competitive advantage. Factors such as international regulations, protection of intellectual property rights, quality standards, the environment, and dispute resolution mechanisms are the main focus in evaluating the competitiveness of Indonesian robusta coffee in the global market. This article proposes a holistic approach that considers not only economic aspects, but also social, environmental and legal factors that influence the robusta coffee industry globally.